Спростити вираз   1)    [latex](1- sin L)(1+sin L) \\ sin^{2} L[/latex]  2)    [latex]cos L-cos L * sin^{2} L [/latex]  3)[latex]tg L*ctg L-cos^{2} L [/latex]

Спростити вираз    1)    [latex](1- sin L)(1+sin L) \\ sin^{2} L[/latex]   2)    [latex]cos L-cos L * sin^{2} L [/latex]   3)[latex]tg L*ctg L-cos^{2} L [/latex]
Гость
Ответ(ы) на вопрос:
Гость
[latex]\frac{(1-sin \alpha )(1+sin \alpha )}{sin^2 \alpha }=\frac{1-sin^2 \alpha }{sin^2 \alpha }=\frac{cos^2 \alpha }{sin^2 \alpha }=ctg^2 \alpha \\\\2)\; cos \alpha -cos \alpha \cdot sin^2 \alpha =cos \alpha (1-sin^2 \alpha )=cos \alpha \cdot cos^2 \alpha =cos^3 \alpha \\\\3)\; tg \alpha \cdot ctg \alpha -cos^2 \alpha =1-cos^2 \alpha =sin^2 \alpha [/latex] [latex]tg \alpha \cdot ctg \alpha =\frac{sin \alpha }{cos \alpha }\cdot \frac{cos \alpha }{sin \alpha }=1\\\\sin^2 \alpha +cos^2 \alpha =1,\to 1-sin^2 \alpha =cos^2 \alpha \\\\1-cos^2=sin^2 \alpha [/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы